1996
DOI: 10.1007/bf02446622
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological analysis of the activity of phenazepam and flunitrazepam administered in superlow doses

Abstract: Benzodiazepine tranquilizers, phenazepam and flunitrazepam, administered to random-bred albino male rats in superlow doses (109-10 -is mol/kg), are shown to exert an anxiolytic effect in the conflicttest, in contrast to the case with the usual doses, the above effect is not accompanied by marked myorelaxant or sedative effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…In support of our previous observations [3], both usual and superlow doses o f phenazepam increased the number of punished drinkings in the conflict test (Table 1), the effect of usual doses was much more pronounced.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…In support of our previous observations [3], both usual and superlow doses o f phenazepam increased the number of punished drinkings in the conflict test (Table 1), the effect of usual doses was much more pronounced.…”
Section: Resultssupporting
confidence: 90%
“…These agents are usually effective in the plus-maze test [8,14,15], and side effects typical of potent benzodiazepines with these drugs are less pronounced o1 absent [14,15]. Previous studies showed [3] that in a conflict situation phenazepam administered in super- low doses acts similarly to anxioselective drugs: it is effective in weak punishing current (0.5 mA) and ineffective in stronger current (1 mA). In these doses the tranquilizer has no side effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect was evaluated by statistically significant increase in the number of punished water takings in the control group rats in comparison with the punished control group at an electrical current strength of 0.5 or 1 mA. The effects of preparations on motor activity were assessed visually by the number of erossings of the lines, which were drawn on the floor under the electrode wires spaced at 5 cm [5].The EEG was recorded under unrestrained behavioral conditions from the rats in which Nichrome electrodes were implanted into the hippocampus and frontal cortex under local anesthesia and Nembutal narcosis (40 mg/kg). The reference electrode was fixed in the nasal bones.…”
mentioning
confidence: 99%
“…Experimental studies of bipathic mode of drug administration showed that phenazepam in ultralow doses (10 -9 -10 -14 mol/kg) exhibited a pronounced anxiolytic effect, not accompanied by side effects characteristic of benzodiazepine tranquilizers (myorelaxant and sedative) [1,2,4].…”
mentioning
confidence: 99%